Improving Students’ Scientific Literacy in Biology Learning Through Problem-Oriented Project-Based Learning (POPBL) Model with Pekerti Worksheet - Sinusi, Nur Suhaiba; Ibrohim, Ibrohim; Rahayu, Sofia Ery (AIBPM Publisher, 2024)
This study investigates the effectiveness of the Problem-Oriented Project-Based Learning (POPBL) model, combined with the Pekerti Worksheet, in improving science literacy among students at Middle School 2 Alla, Enrekang, South Sulawesi. POPBL offers a project-based learning approach centered on real-world issues, complemented by the Pekerti Worksheet, which includes questions, essential concepts, action plans, and initiatives. The study utilized a quasi-experimental design with pre-tests and post-tests in a non-equivalent control group format. A total of 75 eighth-grade students were divided into three groups, and data were collected through observations and tests. Hypotheses were tested using Analysis of Covariance (ANCOVA). The results indicate that students in the POPBL group utilizing the Pekerti Worksheet demonstrated significantly higher science literacy scores than both the POPBL group without the worksheet and the conventional learning group. Statistical analysis confirmed that the integration of POPBL and the Pekerti Worksheet had a substantial positive impact on science literacy (p = 0.000). These findings support the implementation of the POPBL model with the Pekerti Worksheet as an effective approach to foster the Independent Curriculum in Indonesia's junior high schools, contributing to the enhancement of essential 21st-century skills